How do students approach the study of the History of Medicine? Some considerations after the final exams at the first year and fourth year. - Armocida, Emanuele; Nicoli Aldini, Nicolò; Bussolati, Ovidio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Reports about the teaching of the History of Medicine in universities worldwide can be found easily in medical literature. They are often comparative studies in which the opinions provided by the professors are collected and the teaching programs are compared. Our study focuses instead on the relationship between the students and the discipline, what they look for from it, and how their interest changes with the progress of the course of study.Methods: The final tests of the students of two Italian universities, Parma and Bologna, were analyzed, in which the candidate had the ability to choose the topic of discussion and to outline his personal analysis. The course year in which the final examination was faced is different: in the first year in Bologna, in the fourth year in Parma.Results: This survey show that in both universities most students have carried out autonomous research regardless of the educational material made available to them. This attitude can be interpreted as a real interest in the history of medicine, widening their search throughout all the fields of the discipline.Conclusions: These results seem to suggest to teachers of History of Medicine to convey to their students the methodology of historical and epistemological research, giving the student to the pupils the opportunity to become passionate about history in the way he/she prefers. (www.actabiomedica.it)